Measuring the adaptation gap: A framework for evaluating climate hazards and opportunities in urban areas. Issue 66 (December 2016) - Chen, Chen; Doherty, Meghan; Coffee, Joyce; Wong, Theodore; Hellmann, Jessica
Highlights: As cities have numerous concerns and limited resources, prioritizing adaptation options is vital. Options can be prioritized by no-regret, primary, secondary, and tertiary adaptation. The distance between adaptation need and existing efforts can identify an "adaptation gap". An adaptation gap considers climatic risk, uncertainty and cost and irreversibility of option implementation. For Seattle, the no-regret adaptation gap highlights opportunity for decision- makers. Abstract: Urban areas are increasingly seen as having distinct need for climate adaptation. Further, as resources are limited, it is essential to prioritize adaptation actions. At the municipal scale, we suggest that priorities be placed where there is a gap between adaption need and existing adaptation effort. Taking Seattle, USA, as an example, we present this gap in terms of four categories of adaptation options (no-regret, primary, secondary, and tertiary) for the three primary urban hazards—flooding, heat wave, and drought. To do so, we first establish current adaptation need by identifying and categorizing adaptation options. Next, we consider for each option the number of hazards addressed and benefit to and beyond climate adaptation, the projected magnitude of the hazards addressed, the projection's uncertainty, and the required scale and irreversibility of investment. Third, we assessed Seattle's current adaptation efforts by reviewing adaptation plans and related materials. Finally, we identify the distance or "gap" as the proportion of adaptation options not identified by existing adaptation plans. For Seattle, we categorized seven options as no-regret adaptation, five as primary, two as secondary, and three as tertiary. Each level's adaptation gap highlights significant opportunities to take steps to reduce climate risks in key areas.